The value of prostatic specific antigen in the early diagnosis of prostatic cancer: a Greek view - Deliveliotis, Ch.; Alivizatos, G.; Karayiannis, A.; Kontothanasis, D.; Makrychoritis, K.; Lysiotis, P.; Dimopoulos, M.A. (British Journal of Urology, 1995)
Objective To assess whether it is worthwhile to screen asymptomatic men for prostate Cancer using serum prostate specific antigen (PSA) and to determine how many patients could be cured of prostatic carcinoma if detected by screening. Patients and methods Between June 1992 and January 1994 the serum PSA level of 1400 asymptomatic men over 50‐years‐old was assessed. Those men with PSA levels < 4 ng/mL were not evaluated further. Those men with PSA levels of 4–10 ng/mL underwent digital rectal examination (DRE) and transrectal ultrasonog‐raphy (TRUS) and biopsies were taken when there were significant findings on DRE and/or TRUS. If the PSA levels were > 10 ng/mL patients were submitted for DRE and TRUS and. even if both examinations were negative, random biopsies were taken. Where Cancer was detected the tumour was staged and if it was a clinically confined tumour a radical retropubic prostatectomy was performed. The pathological and clinical stages of the disease were then compared. Results The majority of patients (95%) had PSA levels of < 4 ng/mL. Forty‐nine men had PSA levels of 4–10 ng/mL and of these 28 were biopsied, which detected 12 (24.5%) carcinomas. There were 20 men with PSA levels > 10 ng/mL and among them 11 (55%) were found to have carcinomas. Combining these figures, among the 1400 men there were 69 cases with PSA levels >4 ng/mL and, using DRE and TRUS, 23 patients (33%) were diagnosed as having prostatic adenocarcinomas. Among these, one had metastatic disease, three had lymph node micrometast‐ases during surgical exploration and 19 underwent radical prostatectomies. The pathological and clinical stages agreed in only eight patients. Conclusion Only eight patients can be considered as cured because of the screening protocol and even this result is overoptimistic, as the future biological behaviour of these tumours is unknown. Therefore we cannot recommend screening for prostatic carcinoma among asymptomatic men in Greece. Copyright © 1995, Wiley Blackwell. All rights reserved
Keywords: Prostatic carcinoma; Screening; serum PSA level